A review of results of breeding for milk production in the tropics and application of these results to Nigerian conditions - Okali, C. (International Livestock Centre for Africa, 1979)
Small ruminants production in Nigeria was examined to determine their socio-economic contribution. Data on household size, farm size, crop distribution, degree of involvement in the cash economy, farm income and importance of non-farm income; in relation to the number of types of small ruminants kept per household so as to estimate the contribution of small ruminants to household meat consumption and total cash sales of agricultural products in the ILCA surveyed areas included. Some of the socio-economic constraints to intensive small ruminant production, considering labour, capital, infrastructure, marketing facilities and cultural preferences indicated.